Frontispiece: 18F‐Labeling of Sensitive Biomolecules for Positron Emission Tomography. Issue 62 (7th November 2017) - Krishnan, Hema S.; Ma, Longle; Vasdev, Neil; Liang, Steven H.
Abstract : This Review focuses on recent advances in radiochemical methods for incorporating fluorine‐18 into biomolecules via "direct" or "indirect" bioconjugation. Recently developed prosthetic groups and pre‐targeting strategies, as well as representative examples in 18 F‐labeling of biomolecules in PET imaging research studies are highlighted. For more details see the Review by N. Vasdev, S. H. Liang et al. onpage 15553 ff.